As influências do trágico na prosa de Adonias Filho - Reis, Vanessa dos Santos (2013)
This dissetation aims to analyze the presence of tragedy as na essential element in the novels. Os servos da morte (1946), Memórias de lázaro (1952) e Corpo vivo (1962) by Adonias Filho. For this, use is made of the deductive method of literary analysis. At first, we tried to capture the sense of Attic tragedy and the tragic in light of the classical teachings of Aristotle and modern authors such as Nietzsche, Goethe, Vernant and Pierre Vidal-Naquet, Albin Lesky, Mircea Eliade, Paul Harvey and Junito Brandão de Souza. In the novels of Adonias Filho focussed aspects that best configure the tragic sense, now reworked the characterization of characters built from the Greek archetypes, now identifiable in textual elements that make dialogue romance / tragedy more latent, such as the constant interference the narrator, and the presence of fatum like element that drives the gear which leads to a tragic outcome. For being Os servos da morte, Memórias de lázaro y Corpo vivo contemporary novels stand out in them not only the elements purport classical influence, but also the elements break trough the author's peculiar speech. Trough rereadings of myths proposed by Adonias Filho, it is possible demonstrate that fundamental themes permeate the history of literature: the presumed break with old models constitutes, in fact, na element perennial provocateur innovation in literary art, justifying a constant recurrence the classical assumptions. Results of this research work one more contribution to the literary criticism of Adonias Filho son, proving that the novelist renews the tragic and, again, gives universality and timelessness to the tragedy, with undeniable originality and art.